Study of assessment of awareness for screening of cervical cancer in women attending gynecology outdoor patient department - Lal, Neha S.; Kujur, Avinashi; Tiwari, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Nearly every family in the world is touched by cancer, which is now responsible for almost one in six deaths globally. Aim of this study was to access Indian woman’s awareness towards cervical screening methods to promote strategies for increasing its uptake. Methods: A comprehensive questionnaire based cross-sectional observational survey was conducted in Pt. JNM Medical College and Dr. BRAM hospital, Raipur, Chhattisgarh from September 2018 to July 2019. Participants were selected by sampling between 21 to 59 years of age who have given consent for study. Results: Out of 1008 participants only 336 (33.3%) participants were aware about screening of cervical cancer and less than 28% participants were aware about pap smear, time of investigation, method of pap smear, health centre, association of HPV virus with cervical cancer, availability at vaccination, and with regard to risk factors only 27.9% women were aware that there is increased risk of cervical cancer due to multiple partners, 17.6% aware of risk due to increase in number of children’s, 11.1% aware of increase in risk of cervical cancer due to early initiation of sexual activity. Younger women (age 30-35, odds ratio 1.24, 95% CI 0.78-1.32, p-value 0.05), low socioeconomic status (odds ratio 1.74, 95% CI 0.76-2.12, p-value 0.01), education level (≤ secondary education odds ratio 1.64 95% CI 0.85-2.18 p-value 0.000, ≥ higher secondary or above education odds ratio 2.32 95% CI 1.21-2.89 p-value 0.001) and age at marriage (odds ratio 2.21, 95% CI 0.78-2.18, p-value 0.000) all had a significant relationship with the awareness of Pap smear test. Two-third of the females in the study stated that lack of awareness as the major reason for not getting a pap smear while another one- third stated lack of recommendation by health care professionals as major hurdle. Conclusions: This study found that woman’s fear, pain and embarrassment, along with cultural influences, deterred them from undergoing screening.